Vascular leiomyoma of the nasal cavity - Vieira, Joaquim Pedro (2009)
Vascular leiomyoma is a  benign smooth muscle tumor. lt is common in the uterus, alimentary tract, skin and subcutaneous tissue, but uncommon in the head and neck area. We report a case that involved the nasal cavity, an extremely rare location. Treatment options and a review of the literature are discussed.